PERANCANGAN DAN IMPLEMENTASI PENAMPIL NAMA STASIUN UNTUK KERETA API LOKAL BERBASIS MIKROKONTROLLER DENGAN DISPLAY DOTMATRIX - Hari Satriyo Basuki (Teknoin, 2006)
As we know that in the lokal train, sometimes we need information what station in front or already left. In this paper will be discussed about the design and the implementation of a lokal train station name displayer using microcontroller and LEDs. dot matrix. This display should be informative especially for new passengers or passenger who sleep during this travel and also for foreigners. This display will be place in parallel in every wagon near the door. To select the name of the stations is only by pressing the switch which is connected to every controller in the displayer.Keywords : station name displayer, microcontroller, dotmatrix display